Non-Destructive Testing by Magnetic Noise Method of the Quality of Heat Treatment of Steel Samples Obtained by Additive Technology - V. N. Busko; A. P. Kren; G. A. Lanzman (Приборы и методы измерений)
The manufacture of products using additive technologies is accompanied by the unpredictable appearance of inhomogeneity of properties, anisotropy, residual stresses, porosity, and other defects. Therefore, there is a great relevance of non-destructive quality control of products obtained by additive technologies. The purpose of the paper is the experimental investigation of the possibility of testing and evaluation of the quality of heat treatment of three-dimensional and cast samples by non-destructive control methods.The low-alloy steel 09G2S samples, which was obtained by casting and selective laser sintering different modes of subsequent heat treatments were studied. The method of the Barkhausen effect and the instrumented indentation method for measuring the material hardness were applied.It was experimentally established that both methods are highly sensitive to annealed and normalized three-dimensional samples and their rejection. Compared to the hardness measurement method, which is mainly associated with phase-structural changes, the magnetic noise method due to selectivity to other controlled parameters is additionally sensitive to cast samples (at the same time the microstructures of cast and normalized three-dimensional samples are close to each other according to X-ray data).The magnetic noise method can be used as one of the physical methods for evaluation the quality and control of the heat treatment of 3D samples at the manufacturing stage when testing their types and modes, as well as sorting samples.